1955
DOI: 10.1139/v55-168
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence Phenomena in the Critical Region: Iii. Compressibility of Ethylene and Xenon From Light Scattering

Abstract: Turbidity measurements in the region immediately above the critical temperature are used t o calculate values of ( a p l a u )~. These results show that ( a p l a v )~ is a continuously variable function of the density t o within 0.02"C. above the critical temperature. The experiments indicate that there esists no region above T, throughout which (ap/av)T = 0 in ethylene or xenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

1958
1958
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…In previous publications (3,4), the authors reported large vertical gradients in density near the liquid-vapor critical point in one-component systems. These gradients, due t o gravitational compression, were anticipated owing to the large compressibility of a fluid in the critical region.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…In previous publications (3,4), the authors reported large vertical gradients in density near the liquid-vapor critical point in one-component systems. These gradients, due t o gravitational compression, were anticipated owing to the large compressibility of a fluid in the critical region.…”
Section: Introductionmentioning
confidence: 92%
“…I t was, however, shown by Yvon (9) that such concentration gradients are predicted theoretically. Since Rice and Rowden (6) reported a flat apex on the coexistence curve for aniline-cyclohexane, it was of interest to see if this flat top could be ascribed t o concentration gradients by analogy to the gravity effect in one-component systems (3,4,7,8).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations